The Impact of Gendered Policies on Women's Voting Behavior: Evidence from the 2015 British General Election. (3rd April 2023) - Sanders, Anna
ABSTRACT: Political parties often seek to appeal to women voters through policy pledges. However, little is known about how – or whether – these policies influence women's voting behavior. Drawing on focus groups conducted with women voters, I explore how women perceive, experience, and negotiate gendered policies in their voting behavior using the 2015 British General Election as a case study. Overall, I find that "class-based" economic policies pertaining to the sexual division of labor matter to women voters, whereas policies seeking to tackle discrimination against women ("gender status" policies) are comparatively less salient. Crucially, attitudes toward class-based policies differ by life-stage. Taken together, I argue that studies on gender and vote choice should devote greater attention to the electoral context in addition to socioeconomic factors.